Diseño y construcción de un ascensor de 150 kg. de carga neta por 6.10 metros de recorrido, para una persona con discapacidad en la ciudad de Santo Domingo de los Tsáchilas. - Cadena Ramírez, Fabricio Javier (2018)
The present application was carried out in Santo Domingo de los Tsáchilas and establishes a methodology for the design and construction of a 150 kg. elevator with a length of 6.10 meters. For this, it was necessary an analysis of construction and operation alternatives with which the elevator will operate, as well as the use of the Ecuadorian Standard CPE INEN 18: 2000. To this end, the design of the structure and the elements subject to tension and compression are linked to the mandatory safety parameters in each country. With the application of a design based on the efforts of creep of the materials and resistance of the mechanical elements its reliability was determined. The data processing allowed to determine that the materials selected according to the loads to which they have been subjected, are suitable for the construction and operation of the elevator.